A fatal course of hemophagocytic lymphohistiocytosis in a child with homozygous ERCC6L2 defect and heterozygous ADA2 variant: a case report - Lulek, Szymon; Bąbol-Pokora, Katarzyna; Radwańska, Monika; Popiel, Daniel; Reich, Magdalena; Młynarski, Wojciech; Chaber, Radosław (Frontiers in Immunology, 2026)
Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening hyperinflammatory syndrome that may arise secondary to genetic or acquired triggers. Although HLH has been reported in patients with adenosine deaminase 2 (ADA2) deficiency, to date it has not been reported in individuals harboring pathogenic variants in ERCC6L2, a gene typically linked to inherited bone marrow failure. We report a fatal case of HLH in a 2-year-old girl with persistent fever, cytopenias, hepatosplenomegaly, liver failure, and multiorgan dysfunction. Despite targeted HLH therapy, the disease progressed rapidly. Genetic testing identified a homozygous pathogenic variant in ERCC6L2 and a heterozygous ADA2 variant, which we interpret as indicating a susceptibility background to immune dysregulation, with HLH most plausibly occurring as a secondary, trigger-dependent event. No functional validation was performed, and causal inference cannot be made on this basis. To our knowledge, this is the first documented case of HLH in a patient with a homozygous pathogenic ERCC6L2 variant. The co-occurrence of a heterozygous ADA2 variant may have modulated the hyperinflammatory response. These observations highlight the importance of genetic evaluation and suggest—while not proving—a broader spectrum of genetic contexts associated with pediatric HLH; confirmation will require functional studies and replication.